[Architect Julia Morgan] - Sara Holmes Boutelle::::::::: (1980)
Sara Holmes Boutelle, biographer of Julia Morgan, discusses her research on Morgan. [00:00:01] Boutelle states that many people do not realize the Castle at San Simeon is designed by Julia Morgan [00:00:14] The early life of Morgan in Oakland, California [00:00:47] Morgan's experience as a woman in the architectural program at the Ecole des Beaux Arts in Paris [00:01:39] Morgan's first important architectural project in the United States designing a bell tower for Mills College [00:02:28] Morgan's use of local materials to have buildings work in harmony with the landscape [00:02:55] Morgan's employment in reconstructing the Fairmont Hotel after the 1906 earthquake [00:04:35] Her use of skilled craftsmen in Morgan's shingled houses [00:04:58] Typical characteristics of Morgan's designs such as fireplaces and exposed beams [00:05:52] St. John's is an example of eclecticism that combines various styles into something new [00:07:12] Features and details of the King's Daughter's Home in Oakland [00:08:35] The natural qualities of Asilomar on the Monterey Peninsula [00:09:17] Morgan's work building YWCAs that provided urban housing for single women [00:10:42] Features of Morgan's work for the Emmanuel Sisterhood building a residence for young Jewish women [00:11:53] The Honolulu YWCA project that the only project out of state and thus was supervised by mail [00:13:10] The design of Hearst Ranch Headquarters in San Simeon [00:13:32] The design of a combination shop-and-house Morgan designed for one of her favorite craftsmen, Jules Supo [00:14:14] The combination of Californian and European architectural styles in the Chapel of the Chimes in Oakland [00:14:58] The ornate details of the Berkeley City Club as one of Morgan's most impressive buildings [00:16:02] William Randolph Hearst's connection and work with with Julia Morgan [00:16:34] Creating a Bavarian village in Wyntoon for Hearst in Northern California [00:17:09] The construction of the Hearst Castle as a monument for his art collection and center for his media empire [00:17:57] The ornamental designs of the castle [00:18:42] The variety of designs for each of the different buildings at San Simeon [00:19:02] The regal designs of the pools at the castle that reflect Greek and Roman styles [00:19:26] How the back of San Simeon was never finished but it shows how Morgan planned to incorporate Mr. Hearst various european treasures into one design [00:19:58] The small shack that has been left as a tribute to the architect of the building, Julia Morgan [00:20:38] The views from the castle of the surrounding lands [00:20:50] Morgan's vision of San Simeon as a museum and monument rather than a residence [00:21:25] Morgan's honorary degree and recognition of excellence from the University of California